The influence of building information modelling on the absorptive capacity of project-based organisations. (2nd January 2023) - Ahankoob, Alireza; Manley, Karen; Hon, Carol; Drogemuller, Robin
ABSTRACT: Absorptive capacity (AC) is a theoretical construct that measures the capacity of an organisation to absorb knowledge from external sources to sustain competitive advantage. Information dispersion makes it difficult for project-based organisations (PBOs) to absorb new ideas. The current study uses AC theory to examine how the use of building information modelling (BIM) affects the capacity of building contractors to absorb new information and become more competitive. A desktop study of secondary sources was undertaken to assess if there is a potential link between BIM and contractor AC. This revealed that the potential benefits of BIM's technical features are motivated through its functional attributes. Exploratory factor analysis (EFA) was used to clarify the underlying relationship of a cluster of variables. The results of EFA led to the confirmed three categories for BIM functional attributes, including: (1) integration, (2) comprehensibility, and (3) transparency. Multiple regression analysis was used to explore the latent relationship between BIM functional attributes and contractor AC. The regression analysis of survey data, which was gathered from 56 building contractors in Queensland, Australia, showed that the transparency function of BIM functional attributes significantly correlated with acquisition and transformation dimensions of contractor AC. The study confirms a link between BIM and contractor AC, providing further evidence of the importance of BIM in sustaining the competitive advantage of project-based organisations.